Zakat Sebagai Alternatif Pembayaran Pajak dalam Rangka Meningkatkan Kepatuhan Wajib Pajak - Rusydi, M. Khoiru (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2006)
This research tries to describe the system of zakat payment substituting tax payment Because zakat has two dimensions, vertical in relating to Alloh SWT and horizontal in relating to society. In order that zakat is very potential alternatives in developing duty as tax payment to fulfill the obligation of country. In this research is tried new organization structure whichis wished to apply the system of researcher. Key words: zakat, payment substituting